NEW TRAPEZIUM INEQUALITIES FOR GENERALIZED INTEGRAL OPERATORS PERTAINING m-CONVEX FUNCTIONS AND THEIR APPLICATIONS - Kashuri, Artion (Matematichki Bilten, 2019)
The author discovered an identity for a generalized integral operator via differentiable function. By using this integral equation, we derive some new bounds on Hermite-Hadamard type integral inequalities for differentiable functions that are in absolute value at certain powers \(m\)-convex. By taking suitable choices of function, some interesting results are obtained. At the end, some applications of presented results to special means and new error estimates for the trapezium formula have been analyzed. The ideas and techniques of this paper may stimulate further research in the field of integral inequalities.